BOOK REVIEWS (Journal of Finance, 1962)
Book reviewed in this article: Business Finance : Business Cycles and Forecasting . By E lmer C lark B ratt . Insurance : The Economic Impact of Federal Loan Insurance . By G eorge F. B reak . Insurance: Its Theory and Practice in the United States . By A lbert H. M owbray and R alph H. B lanchard . Commercial Credit Insurance as a Management Tool . By C lyde W illiam P helps . International Finance : Grants, Loans, and Local Currencies ¦ Their Role in Foreign Aid . By R obert E. A sher . Joint International Business Ventures . Edited by W olfgang G. F riedmann and G eorge K almanoff . The Canadian Dollar, 1950–1958 . By P aul W onnacott . Investments : Investments . By G eorge W. D owrie , D ouglas R. F uller , and F rancis J. C alkins . Information and Investment . By G. B. R ichardson . Money and Banking : Money in Motion . By A rthur D ahlberg . Economics of Money and Banking , By G eorge N. H alm . Money and Banking . By C. L owell H arriss . What Price Economic Growth? Edited by K laus K norr and W illiam J. B aumol . Growth and Prosperity without Inflation . By J ohn P. W ernette . Public Finance : The Role of Debt in the Economy . By H elen J. C ooke . Taxes for the Schools . By R oger A. F reeman . The Tax Exemption of Cooperatives . By R obert T. P atterson . Real Estate Finance : Real Estate Finance . By H enry E. H oagland and L eo D. S tone . The Postwar Residential Mortgage Market . By S aul B. K laman . Related Disciplines : Conceptual Foundations of Business . By R ichard E els and C larence W alton . Probability: A First Course . By F rederick M osteller , R obert E. K. R ourke , and G eorge B. T homas , J r . Probability with Statistical Applications . By F rederick M osteller , R obert E. K. R ourke , and G eorge B. T homas , J r . Keynesian Economics in the Stream of Economic Thought . By H arlan L. M c C racken .